2010
DOI: 10.3109/07357907.2010.494321
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Breast Cancer (Part I): Epidemiology, Risk Factors, and Risk Assessment Tools

Abstract: Advances in breast cancer research have led to declining death rates from this disease because of early detection through mammographic screening and improved therapy for breast cancer. The concept that breast cancer, in some cases, can be prevented has been explored over the last three decades. This article, part I of a two-part series, will focus on the epidemiology, the risk factors associated with breast cancer, and the available risk assessment tools, which can help define who should be considered for risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
40
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 69 publications
0
40
1
6
Order By: Relevance
“…The main cause of this mortality is the metastatic spread to other organs (1). Metastasis occurs when tumor cells acquire invasive features (2) and the ability to escape from antitumor immunity (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…The main cause of this mortality is the metastatic spread to other organs (1). Metastasis occurs when tumor cells acquire invasive features (2) and the ability to escape from antitumor immunity (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer remains the leading cause of death for women of 35 to 65 years old (1). Gene expression studies have shown the heterogeneity of the disease and identified at least 5 clinically relevant molecular subtypes of breast tumors: luminal A, luminal B, ERBB2, basal, and normal-like (2).…”
Section: Introductionmentioning
confidence: 99%
“…Latin America and the Caribbean are ranked in the middle, with an age-standardized incidence rate of 40 per 100,000 women [2]. As documented in the literature, a mixture of demographic, hereditary, economic, environmental, and lifestyle risk factors account for this variability [3]. However, differences in the capacity of a country's health system for detection and diagnosis, as well as case and death registration, also affect the disease burden.…”
Section: Introductionmentioning
confidence: 99%